TECHNOLOGICAL SENTATIONS OF SOLVING THE PROBLEM OF DISCIPLINE AND EVALUATION OF STUDENTS AS A FACTOR OF IMPROVING THE QUALITY OF THE EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2009)
Technological sentation of the solution of discipline and student evaluating problem are exposed in the article as a factor of the increase of the quality of educational process.